Nano protective membrane coated wheat to resist powdery mildew - Zhang, Huilan; Yuan, Meng; Gao, Yameng; Su, Pengfei; Jia, Huiling; Tang, Caiguo; Meng, He; Wu, Lifang (Frontiers in Plant Science, 2024)
1. The powdery mildew inhibitor KTP is composed of 1 g/L kaolin, 2 g/L nanotitanium dioxide and 8% (v/v) liquid paraffin.2. KTP is formed by hydrogen bonding and electrostatic attraction between components.3. The prevention effects of KTP in the pot and field experiments were 98.45% and 83.04%, respectively.4. The yield of wheat increased significantly after the control of powdery mildew by KTP.5. KTP delayed the germination of powdery mildew spores on the leaf surface and inhibited the formation of mycelia.